Effect of concurrent chemoradiation with cisplatin versus concurrent chemoradiation with carboplatin in locally advanced carcinoma cervix: A quasi-experimental study - Syed Md. Asadul Hoque; Uday Kumar Sarkar; Mohammad Rahamatullah; Newton Kumar Sarker; Md Jamal Uddin; Md Abdul Bari (Bangabandhu Sheikh Mujib Medical University Journal)
Background: The standard approach for locally advanced cervical cancer is concurrent chemoradiation with platinum agents, preferably cisplatin. This study was aimed at comparing the treatment response and toxicity of carboplatin-based versus cisplatin-based concurrent chemoradiation in locally advanced carcinoma of the cervix.